Reign. The complete first season [videorecording (DVD)] - McCarthy, Laurie; Sengupta, Stephanie (CBS Studios, Inc, 2014)
Ever since Mary Stuart, Queen of Scotland, was a little girl, the English have wanted her country and her crown. As a teenager, Mary is sent to France to wed its next king to save herself and her people. Waiting at the French Court is the gorgeous Prince Francis, his illegitimate half-brother Sebastian, a king on the brink of madness, a scheming queen, and the seer Nostradamus with a devastating prophecy.